Applications of calcium channel blockers in psychiatry: pharmacokinetic and pharmacodynamic aspects of treatment of bipolar disorder. (2nd January 2019) - Dubovsky, Steven L.
ABSTRACT: Introduction : Calcium channel blockers (CCBs) comprise a heterogeneous group of medications that reduce calcium influx and attenuate cellular hyperactivity. Evidence of hyperactive intracellular calcium ion signaling in multiple peripheral cells of patients with bipolar disorder, calcium antagonist actions of established mood stabilizers, and a relative dearth of treatments have prompted research into potential uses of CCBs for this common and disabling condition. Areas covered : This review provides a comprehensive overview of intracellular calcium signaling in bipolar disorder, structure and function of calcium channels, pharmacology of CCBs, evidence of efficacy of CCBs in bipolar disorder, clinical applications, and directions for future research. Expert opinion : Despite mixed evidence of efficacy, CCBs are a promising novel approach to a demonstrated cellular abnormality in both poles of bipolar disorder. Potential advantages include low potential for sedation and weight gain, and possible usefulness for pregnant and neurologically impaired patients. Further research should focus on markers of a preferential response, studies in specific bipolar subtypes, development of CCBs acting preferentially in the central nervous system and on calcium channels that are primarily involved in neuronal signaling and plasticity.